PEMANFAATAN MEDIA CD INTERAKTIF DALAM PEMBELAJARAN BERBICARA BAHASA ARAB KELAS VIII A MTs N KENDAL TAHUN AJARAN 2011/2012 (Universitas Negeri Semarang, 2012)
Speaking skills is one of the language skills to be achieved in the teaching of languages ​​including Arabic. But in reality, many students still find difficulty in learning to speak Arabic. Cause of the difficulties faced by students in part because the media are applied by the subject teachers Arabic unattractive and boring so that students are reluctant to participate actively in the activities of Arabic speakers. Therefore, the use of interactive media CD media is expected to provide an opportunity for students to express ideas or thoughts as possible especially on speaking skills. The problem in this study are: (1) How to increase Arabic speaking skills after the applied media interactive CD in class VIII A Kendal MTs academic year 2011/2012?. (2) how the response and interest of students of class VIII A Kendal MTs academic year 2011/2012 as applied to media interactive CD?. The purpose of this study, namely: (1) to determine the Arabic speaking skills improvement class VIII A Kendal MTs after application of interactive CD media. (2) to study the response and interest of students of class VIII A Kendal MTs academic year 2011/2012.